2007
DOI: 10.21168/rbrh.v12n4.p103-110
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Desempenho de Modelo Hidrológico de Balanço Hídrico na Sub-bacia de Caraúbas, em anos de El Niño e La Niña

Abstract: Visando aplicar o balanço hídrico à superfície para outras bacias hidrográficas no semi-árido avaliou-se o desempenho do modelo desenvolvido por Galvíncio em 2005 e 2006, em anos de El Nino e La Nina, na sub-bacia hidrográfica de Caraúbas, localizada no semi-árido do Nordeste do Brasil (NEB). No balanço hídrico foram utilizados os totais diários e anuais precipitados, no período de 1973 a 1990 em cinco postos pluviométricos, localizados no âmbito da sub-bacia em estudo; os totais anuais evaporados; vazões diár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…The opposite was also observed in a normal year preceded by dry year. Galvíncio and Sousa (2007) obtained similar results for the Cariri Paraibano, that is a Caatinga area. In the present research, it was observed that occurred ten hydrological years considered neutral from the point of view of ENOS phenomenon, but two of them occurred subsequently to La Niña events, 1985/86 and 1996/97, in these two periods the annual NPP values were higher than mean plus the standard deviation of the neutral periods.…”
Section: Net Primary Production In Neutral Yearssupporting
confidence: 58%
“…The opposite was also observed in a normal year preceded by dry year. Galvíncio and Sousa (2007) obtained similar results for the Cariri Paraibano, that is a Caatinga area. In the present research, it was observed that occurred ten hydrological years considered neutral from the point of view of ENOS phenomenon, but two of them occurred subsequently to La Niña events, 1985/86 and 1996/97, in these two periods the annual NPP values were higher than mean plus the standard deviation of the neutral periods.…”
Section: Net Primary Production In Neutral Yearssupporting
confidence: 58%